Source, and effect of Bacterial Kidney Disease (BKD) in Icelandic aquaculture - Snorri Stefánsson 1992- (2020)
One very important factor for healthy and prospering fish farming is good knowledge about infectious diseases and the best way to handle those diseases. Bacterial Kidney Disease (BKD) is caused by the Gram-positive bacterium Renibacterium salmoninarum (Rs) and since the start of fish farming in Iceland, Rs has caused significant problems in the industry and is without a doubt the disease that has caused the most damage in aquaculture the last decades. Rs is common and widely distributed in wild salmonids around Iceland and therefore the use of untreated surface water as a water source, opens possibilities for the pathogen to enter the aquaculture system. Three land-based salmonid farms took part in this project, all of which have experienced BKD outbreaks in recent years. All these farms have used, to a varying degree, water from nearby mountain brooks as a water supply. Consequently, suspicions arose whether this brook water might be the source of Rs-infection in the farms. Available data on the presence of salmonids in these brooks were wage or hardly existing, and no data existed on the Rs-status of the salmonids inhabiting them. The results strongly suggest the BKD outbreaks, experienced recently in all three farms, can be traced to Rs-infected water from nearby brooks the farms used as water source. Since there are neither active vaccines nor antibiotics available against the disease, the most effective way to minimize the occurrence and effect of BKD is to prevent the bacterium from entering land-based fish farms, by using solely UV-treated borehole water. Ein af grunnforsendum farsæls og arðvænlegs fiskeldis er þekking á eðli sjúkdóma og áreiðanlegum aðferðum til að greina og meta smitsjúkdómavalda. Því er afar mikilvægt að það sé í eins góðri sátt við náttúrulegt umhverfi þess og frekast er unnt. Í þessu sambandi hefur nýrnaveiki (BKD - Bacterial Kidney Disease) oft verið nefnd. Hún orsakast af bakteríunni Renibacterium salmoninarum og er án efa sá sjúkdómur sem valdið hefur hvað mestu tjóni síðustu ...